The Effect of Auditory, Intellectually, And Repetition (Air) Model on Students’ Reading Comprehension at Eleventh Grade of SMAN 8 South Bengkulu - Riswanto, Riswanto; Afriani, Zelvia Liska; Adini, Vesi Putri (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
The purpose of this study was to determine whether there was an effect of the Auditory, Intellectually, And Repetition (Air) Model on Reading Comprehension in understanding the explanation text. This study used a Quasi-Experimental research design. In this study, the sample size was 48 students, including 24 students in the experimental class (XI IPS 2) and 24 students in the control class (XI IPS 1) at SMAN 8 South Bengkulu taken by purposive sampling. The experimental class has given the treatment using the Auditory, Intellectually, And Repetition AIR Model, while the control class did not use the AIR Model. The researchers collect data by administering tests twice, namely a pretest and a post-test. Prior to administering the post-test, the researcher administered four treatments in the experimental and control classrooms using different teaching models. The instrument employed in this study was a set of 20 valid multiple-choice questions. The data from the pre-test and post-test were examined using the t-test. The learning outcomes were as follows: First, the experimental class's mean score was 37,29, whereas the control class was 40,83. And for the post-test findings reveal that the experimental class has an average value of 81.25 while the control class has an average value of 70.42. Second, the sample score of the independent T-test shows the significant value (2 tailed) is 0,000 <0.05. In other words, Ho was rejected and Ha was accepted. In brief, Auditory, Intellectually, And Repetition (AIR) Model can be one of effective ways in teaching reading for eleventh grade students.